Analyzing the impact of human leukocyte antigen mismatch on the incidence of prostate cancer and the advantage of T cell therapy in patients after kidney transplantation based on the United Network for Organ Sharing database - Gao, Yang; Li, Jingjing; Mao, Jiaxi; Jiang, Aijun; Guo, Wenyuan; Fu, Shangxi (Frontiers in Oncology, 2025)
BackgroundWe aim to analysis the impact of Human Leukocyte Antigen (HLA) mismatch between kidney transplant donors and recipients on the incidence of prostate cancer after kidney transplantation (KT). Meanwhile, understanding the use of T cell therapy is of great importance after kidney transplantation from the perspective of prostate cancer occurrence.MethodsA retrospective study was conducted on kidney transplant recipients based on the United Network for Organ Sharing (UNOS) database from 2000 to 2019. General demographic data, socio-economic and educational data, personal medical history, immunosuppressive therapy regimens, and HLA typing of donors and recipients were collected to analyze the impact of: (1) baseline patient characteristics; (2) HLA mismatch; and (3) HLA subtype mismatch on the incidence of prostate cancer after transplantation.ResultsA total of 268–994 kidney transplant recipients were included, with 1–910 newly diagnosed prostate cancer patients after surgery. Both univariate and Cox multivariate analysis discovered that the use of T cell therapy could reduce the risk of prostate cancer after KT [0.89(0.86 0.91)]. We also found HLA mismatch ≥ 3 is a risk factor of prostate cancer after transplantation [1.07(1.02 1.11)]. Further subgroup analysis was conducted on HLA mismatch. The Cox multivariate analysis of HLA-A (0–2), HLA-B (0–2), and HLA-DR (0–2) mismatch showed that 2-mismatch in HLA-A and HLA-B was a risk factor of prostate cancer after KT [1.19(1.01 1.40)]; 2-mismatch and 1-mismatch were both risk factors of prostate cancer after KT in the HLA-DR group [1.32(1.13 1.54)], [1.20(1.03 1.39)].ConclusionsFrom the perspective of prostate cancer occurrence after transplantation, the use of T cell therapy is of great significance. HLA mismatch ≥ 3 was a risk factor of prostate cancer after KT. HLA-A and HLA-B 2-mismatch were risk factors of prostate cancer after KT, while HLA-DR 1-mismatch and 2-mismatch were both risk factors of prostate cancer after KT. This research contributed to the focus on the relationship between induction therapy and cancer occurrence after KT, and also provide guidance for reasonable selections of HLA typing of prostate cancer before KT.